2003
DOI: 10.1136/oem.60.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response patterns for vibration-induced white finger

Abstract: Aims: To investigate alternative relations between cumulative exposures to hand-transmitted vibration (taking account of vibration magnitude, lifetime exposure duration, and frequency of vibration) and the development of white finger (Raynaud's phenomenon). Methods: Three previous studies have been combined to provide a group of 1557 users of powered vibratory tools in seven occupational subgroups: stone grinders, stone carvers, quarry drillers, dockyard caulkers, dockyard boilermakers, dockyard painters, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
127
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 16 publications
8
127
0
2
Order By: Relevance
“…A recent study 34) indicated that the unweighted acceleration was better than the ISO-weighted acceleration for the assessment of the vibration-induced white finger. Because the major vibration components of most powered hand tools are equal to or less than 250 Hz 31) , the finger TAB-weighted acceleration is highly correlated to the unweighted acceleration, as presented in Table 1.…”
Section: Evidence Supporting the Tab And Bfb Weighting Methodsmentioning
confidence: 99%
“…A recent study 34) indicated that the unweighted acceleration was better than the ISO-weighted acceleration for the assessment of the vibration-induced white finger. Because the major vibration components of most powered hand tools are equal to or less than 250 Hz 31) , the finger TAB-weighted acceleration is highly correlated to the unweighted acceleration, as presented in Table 1.…”
Section: Evidence Supporting the Tab And Bfb Weighting Methodsmentioning
confidence: 99%
“…Hence, the finger TAB weighting method is consistent with the unweighted acceleration method, which is recommended by NIOSH as an alternative method for finger risk assessment 59) . A recent epidemiological study also reported that the unweighted acceleration was better than ISOweighted acceleration for predicting VWF 60) . Another recent application of the transmitted vibration is to check the dc-shift of the acceleration signal 61) .…”
Section: Vibration Transmissibilitymentioning
confidence: 99%
“…Since the 1980's, some investigators have pointed out that the method overestimates the low frequency effect and others have pointed out an underestimation of the high frequency effect [2][3][4][5] . We need a new method of frequency weighting that is medically proven.…”
Section: Introductionmentioning
confidence: 99%